2009
DOI: 10.1152/ajpendo.90874.2008
|View full text |Cite
|
Sign up to set email alerts
|

Small G proteins as key regulators of pancreatic digestive enzyme secretion

Abstract: Small GTP-binding (G) proteins act as molecular switches to regulate a number of cellular processes, including vesicular transport. Emerging evidence indicates that small G proteins regulate a number of steps in the secretion of pancreatic acinar cells. Diverse small G proteins have been localized at discrete compartments along the secretory pathway and particularly on the secretory granule. Rab3D, Rab27B, and Rap1 are present on the granule membrane and play a role in the steps leading up to exocytosis. Wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 128 publications
(175 reference statements)
0
47
0
1
Order By: Relevance
“…Moreover, work from this laboratory and others have suggested that Rab3D may associate with subpopulations of mature ZG [19,20]. Despite the fact that numerous approaches have been employed to elucidate the function of Rab3D, the exact role of this GTPase in exocrine cells remains controversial (for review, see 21). Because of its localization on the ZG membrane, Rab3D was originally believed to be involved in late events in exocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, work from this laboratory and others have suggested that Rab3D may associate with subpopulations of mature ZG [19,20]. Despite the fact that numerous approaches have been employed to elucidate the function of Rab3D, the exact role of this GTPase in exocrine cells remains controversial (for review, see 21). Because of its localization on the ZG membrane, Rab3D was originally believed to be involved in late events in exocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…These secretory vesicles are separated from the apical plasma membrane by a dense actin network, termed the "terminal web" (5,6). In addition, several secretion-supporting roles have been assigned to subapical actin.…”
mentioning
confidence: 99%
“…The most highly conserved and best studied members of the Rho family, Rho1/A, Rac1 and Cdc42, play a crucial role in tethering and fusion of vesicles during regulated exocytosis (Ory & Gasman, 2011;Ridley, 2006;Williams, et al, 2009). Most Rho GTPases transiently localize at the plasma membrane, after being targeted to specific phosphoinositide-containing sub-domains.…”
Section: Rho Gtpases and Assembly Of The Plasma Membrane Exocyst Complexmentioning
confidence: 99%